MENUMBUHKAN SELF EFFICACY KARYAWAN PT WORLD INNOVATIVE TELECOMUNICATION KEDIRI - Atiani, Sela; Buniarto, Edwin Agus; Saptaria, Lina (Arthavidya Jurnal Ilmiah Ekonomi, 2025)
Employee self-efficacy is an important factor that contributes to employee performance, job satisfaction, and organizational commitment. This research aims to analyze leaders' strategies in growing employee self-efficacy at PT World Innovative Telecommunication Kediri. This research uses a qualitative descriptive approach with purposive sampling technique. Data collection was carried out through observation, interviews and documentation. The main informants in this research are trainer managers, supervisors and promoters who have an important role in implementing leadership strategies and establishing self-efficacy in the work environment. The data analysis technique consists of four main stages, namely data collection, data reduction, data presentation, and drawing conclusions. The research results show that leaders' strategies for cultivating self-efficacy in PT World Innovative Telecommunication Kediri employees include: communication, direct meetings, discussion forums, training, coaching and mentoring, financial and moral support, providing reminders. Several factors were found that strengthen and weaken the process of increasing self-efficacy. This research is important for creating the right strategy to support the growth of employee self-efficacy in the workplace so that it has an impact on improving employee performance and welfare.